NT-proBNP Cut-off Values for Risk Stratification in Acute MI and Comparison with Other Risk Assessment Scores. (2022) - Tan, Shirley Siang Ning; Koh, Keng Tat; Fong, Alan Yean Yip; Bujang, Mohammad Adam bin; Tiong, Lee Len; Cham, Yee Ling; Ho, Kian Hui; Tan, Chen Ting; Khaw, Chee Sin; Amin, Nor Hanim Mohd; Oon, Yen Yee; et al.
No abstract available